Handbook of specialty elements in architecture - Alpern, Andrew (New York : McGraw Hill Education, 1982)
The professions of architecture and interior design often demand of their practitioners a significant amount of knowledge in specialized fields beyond the normal realm of practice. Obtaining this knowledge for the infrequent projects that require it can mean timeconsuming research and the tracking-down and acquisition of an extensive library of reference books and manufacturers' catalogues. This handbook obviates all that. It gathers together in one convenient volume the essentials of twelve specialty areas of concern to architects and designers. Presented in twelve chapters, this material gives the reader a sound general understanding of each subject specialty as well as offering a wealth of specific working data.
1. Audiovisual communications -- 2. Exterior plantings -- 3. Trees and plants for interior design -- 4. Sculpture -- 5. Interior art -- 6. Adult outdoor recreation facilities -- 7. Juvenile play areas -- 8. Decorative pools and fountains -- 9. Exterior lighting -- 10. Flagpoles -- 11. Signage -- 12. Designing for the disabled
Includes bibliographical references and index.
Keywords: ARCHITECTURE